Harvard Business Review on Talent Mgmt (Harvard Business Review Paperback Series) - Harvard Business School Publishing Corporation (Harvard Business Press, 2008)
If great talent is hard to find, it's even harder to keep. In today's competitive world, you need the best and the brightest on your team in order to stay ahead of the game. If you lose your key talent, you may find that you're also losing out on crucial business opportunities. This valuable collection offers insights and strategies to make sure you recognize--and retain-- your company's vital talent.